Computer program usage in sport organizations and computer competencies desired by sport organization personnel - Diacin, M. J.; VanSickle, J. L. (International Journal of Applied Sports Sciences, 2014)
The purpose of this study was to investigate the specific computer programs used by sport organization personnel, the tasks they completed with those programs, and the expectations personnel possessed with regard to computer competencies they would expect from job applicants who hold a degree in sport management. Thirty-five practitioners employed at various sport organizations participated in semistructured interviews. Participants utilized programs within Microsoft Office (e.g., Word, Excel) and Adobe Creative Suite (e.g., InDesign, Photoshop) to complete essential job tasks. Various specialty programs were also utilized. Job candidates were expected to possess familiarity and competence with programs used by the participants.